(untitled) (European Journal of Pure and Applied Mathematics, 2026)
A new structure, referred to as a modified JS modular metric space, is introduced in this paper. Fixed point results for a class of hybrid contractions are studied within this framework. An example is provided to illustrate the main findings and to emphasize the distinctions from existing results in the literature. In addition, one of the established theorems is applied to derive new criteria for the existence of solutions to a certain class of integral equation.